Lurasidone versus treatment as usual for cognitive impairment in euthymic patients with bipolar I disorder: a randomised, open-label, pilot study. (March 2017) - Yatham, Lakshmi N; Mackala, Sylvia; Basivireddy, Jayasree; Ahn, Sharon; Walji, Nazlin; Hu, Chen; Lam, Raymond W; Torres, Ivan J
Summary: Background: Cognitive impairment is present in euthymic patients with bipolar disorder and correlates with impairments in everyday functioning. We aimed to examine the efficacy of lurasidone adjunctive therapy compared with treatment as usual (TAU) in improving cognition. Methods: For this randomised, open-label, pilot study, we recruited patients aged 19–65 years with euthymic bipolar I disorder from the Mood Disorder Centre in UBC Hospital (Vancouver, Canada). We included patients who were taking lithium, or valproate, or an atypical antipsychotic, or a combination of these for mood stabilisation and who showed reduced cognitive functioning (SD≤ −0·25 relative to demographics-corrected norms) on either the Trail Making Test-B or the California Verbal Learning Test-II. Patients were randomly assigned using a randomised block design with a block size of four to TAU or lurasidone adjunctive therapy (20–80 mg/day) for 6 weeks. A research coordinator masked to group allocation administered the International Society for Bipolar Disorders Battery for Assessment of Neurocognition (ISBD-BANC) at baseline and at endpoint. The primary outcome was change in global cognition score, which consisted of the mean demographics-corrected t -score value of the several ISBD-BANC measures, analysed in all patients who completed both tests. This trial is registered onClinicalTrials.gov, numberNCT02147379 . Findings: Between July 2, 2014, and Oct 19, 2015, 34 patients were randomly allocated to lurasidone adjunctive therapy (17 patients) or TAU (17 patients). Two patients from each group did not complete the study. The mean lurasidone dose was 48·24 (SD 15·90) mg/day. Lurasidone adjunctive therapy was more effective than TAU in improving the primary efficacy measure of ISBD-BANC global cognition score (mean difference 2·92 [95% CI 0·27–5·57]; time × treatment interaction F =5·09; p=0·032). The between-group effect size (0·82) on baseline versus study-end difference scores in the ISBD global cognition score was of moderate to large magnitude. The magnitude of benefit with lurasidone adjunctive therapy in improving global cognition (effect size 0·46) was greater compared with the improvement observed in the TAU group (0·04). Adverse events were reported by nine (60%) patients in the luradisone group and two (13%) in the TAU group. Interpretation: Our results provide some preliminary evidence for the efficacy of lurasidone in improving cognition in euthymic patients with bipolar I disorder. The strengths of this study were the characterisation of the sample and use of tests sensitive to cognitive impairment in bipolar disorder. Its limitations were the sample size and inability to completely control for other medication use. Larger double-blind trials are warranted to investigate this further. Funding: Sumitomo Dainippon Pharma.